5-hydroxymethylcytosine: a potential therapeutic target in cancer. (October 2014) - Rodger, Euan J; Chatterjee, Aniruddha; Morison, Ian M
The ten-eleven translocation enzymes catalyze the conversion of 5-methylcytosine to 5-hydroxymethylcytosine, a distinct epigenetic mark that has an integral role in active demethylation. Genes that regulate the distribution and amount of 5-hydroxymethylcytosine in the genome could be suitable therapeutic targets to correct abnormal methylation in cancer. Here, we present an overview of the role of the 5-hydroxymethylcytosine pathway in human disease and discuss the emergence of innovative techniques that can map the distribution of 5-hydroxymethylcytosine at high resolution. In the context of current epigenetic therapies and by using recent functional studies, we propose plausible mechanisms to target the 5-hydroxymethylcytosine pathway in cancer. As the study of 5-hydroxymethylcytosine is still in its infancy, we provide future perspectives.